De novo transcriptome assembly facilitates characterisation of fast-evolving gene families, MHC class I in the bank vole (Myodes glareolus) - Migalska, M; Sebastian, A; Konczal, M; Kotlík, P; Radwan, J (Heredity, 2017)
The major histocompatibility complex (MHC) plays a central role in the adaptive immune response and is the most polymorphic gene family in vertebrates. Although high-throughput sequencing has increasingly been used for genotyping families of co-amplifying MHC genes, its potential to facilitate early steps in the characterisation of MHC variation in nonmodel organism has not been fully explored. In this study we evaluated the usefulness of de novo transcriptome assembly in characterisation of MHC sequence diversity. We found that although de novo transcriptome assembly of MHC I genes does not reconstruct sequences of individual alleles, it does allow the identification of conserved regions for PCR primer design. Using the newly designed primers, we characterised MHC I sequences in the bank vole. Phylogenetic analysis of the partial MHC I coding sequence (2-4 exons) of the bank vole revealed a lack of orthology to MHC I of other Cricetidae, consistent with the high gene turnover of this region. The diversity of expressed alleles was characterised using ultra-deep sequencing of the third exon that codes for the peptide-binding region of the MHC molecule. High allelic diversity was demonstrated, with 72 alleles found in 29 individuals. Interindividual variation in the number of expressed loci was found, with the number of alleles per individual ranging from 5 to 14. Strong signatures of positive selection were found for 8 amino acid sites, most of which are inferred to bind antigens in human MHC, indicating conservation of structure despite rapid sequence evolution.
Keywords: exony; Multigene Family; transkriptom; genetická variace; Genotype; fylogeneze; High-Throughput Nucleotide Sequencing; Exons; Phylogeny; Transcriptome; DNA Primers; hlavní histokompatibilní komplex; Animals; zvířata; vysoce účinné nukleotidové sekvenování; Arvicolinae; myši; DNA primery; genotyp; Alleles; Genetic Variation; multigenová rodina; Mice; geny MHC třídy I; alely; Major Histocompatibility Complex; Genes, MHC Class I